How will the court decide? Tax experts and the estimation of tax risk - Kay Blaufus; Jonathan Bob; Matthias Trinks (Arbeitskreis Quantitative Steuerlehre (arqus), 2013)
Tax accounting and tax law concern the probability thresholds that can require the taxpayer to estimate the likelihood that a tax position would be upheld by a court. Tax complexity and the consequent ambiguity results in a reliance by most taxpayers on a tax expert estimate of this likelihood. This study examines whether the tax experts are able to accurately forecast the outcome of tax court decisions and compares tax expert predictions to those of laymen. Our results reveal no significant differences with respect to the forecasting performance of professional tax advisors and laymen. Moreover, the tax advisors exhibit a significantly higher level of overconfidence compared to laymen and the degree of overconfidence increases with professional experience. A comparison of two groups of tax experts, tax advisors and revenue agents demonstrates that the tax advisors exhibit the highest level of overconfidence and form stronger appeal recommendations that indicate a type of advisor bias.
Keywords: M40; K20; H20; 330; tax risk; overconfidence; client advocacy; tax controversy; forecasting